Determining mobile payment adoption: A systematic literature search and bibliometric analysis - Abdullah (Taylor & Francis Group, 2021)
Scholarly interest in the field of m-payment has gained prominence in the last decade owing to the shift in consumer spending patterns. However, only limited numbers of review studies are available on the topic. To overcome the limitation, the paper comprehensively reviewed the content of existing literature available on m-payment to improve understanding of the current state of knowledge. The present research paper reviews peer-reviewed literature available in the Scopus database for the period 2005‑2020. A systematic literature search using the Scopus database was undertaken resulting in a total of 56 studies published in 44 peer-reviewed International journals. The present study reviews the publication trend in the field of m-payment, influential articles and most prolific and influential authors. Thereafter, a bibliometric analysis using VOS Viewer was carried out to identify thematic clusters. Construction of the network map using bibliographic coupling and co-citation analysis reveals interesting patterns and themes in the field of m-payment. Our study provides a better understanding of the field of m-payment and based on the results future avenues were proposed.